Money Talk: Membangun Literasi Keuangan dan Kewirausahaan Siswa SMK - Riani Sukma Wijaya; Ratnawati Raflis; Rahmaita Rahmaita; Murniati Murniati; Indrayeni Indrayeni; Ingra Sovita; Nini Nini (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
The program “Money Talks: When Gen Z Manages Money and Their Own Business” was designed as an educational effort to improve financial literacy and entrepreneurial skills among vocational high school (SMK) students. Initial observations showed that although students had a strong interest in entrepreneurship, many still lacked a basic understanding of financial management, were not accustomed to recording income and expenses, and tended to display consumptive behavior. This activity aimed to equip students with the ability to manage personal finances and small businesses through an applicative and contextual learning approach. The methods used included socialization on simple financial record-keeping and mentoring in entrepreneurial practice. The results showed an improvement in students’ understanding of the difference between needs and wants, budgeting, pocket money management, and the importance of saving. In addition, students began to realize that business opportunities can start from simple ideas that match their interests and skills.